2005
DOI: 10.1021/ja052604e
|View full text |Cite
|
Sign up to set email alerts
|

Ru2(ap)4(σ-oligo(phenyleneethynyl)) Molecular Wires:  Synthesis and Electronic Characterization

Abstract: Reported in this contribution are the synthesis, characterization, and charge transport properties of wire-like Ru2(ap)4(OPEn), where ap is 2-anilinopyridinate and OPE is -(CCC6H4)nSCH2CH2SiMe3 with n = 1 (1) and 2 (2). Scanning tunneling microscopy (STM) measurements of compound 2 inserted into a SAM of C11 thiol reveal that molecule 2 exhibits (i) the stochastic switching characteristic of wire molecules embedded in insulating SAMs and (ii) higher conductivity than the C11 thiol SAM. More importantly, analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
90
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 19 publications
3
90
0
Order By: Relevance
“…[21][22][23] Demonstrating the promise of Ru 2 -alkynyl species as molecular wires, STM (scanning tunneling microscopy) studies of [Ru 2 (ap) 4 -s-(CCC 6 H 4 ) 2 SÀ] embedded in an alkane thiol matrix revealed a significantly improved molecular conductance relative to that of an OPE of similar length. [24] Previously, we reported a series of symmetrical [Ru 2 -A C H T U N G T R E N N U N G (dmba) 4 A C H T U N G T R E N N U N G (C CAr) 2 ] compounds, in which DMBA is N,N'-di-…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Demonstrating the promise of Ru 2 -alkynyl species as molecular wires, STM (scanning tunneling microscopy) studies of [Ru 2 (ap) 4 -s-(CCC 6 H 4 ) 2 SÀ] embedded in an alkane thiol matrix revealed a significantly improved molecular conductance relative to that of an OPE of similar length. [24] Previously, we reported a series of symmetrical [Ru 2 -A C H T U N G T R E N N U N G (dmba) 4 A C H T U N G T R E N N U N G (C CAr) 2 ] compounds, in which DMBA is N,N'-di-…”
Section: Introductionmentioning
confidence: 99%
“…[6] Moreover, a combination of both types of building blocks, organic and organometallic ones, has been elegantly developed by Murahashi and Kurosawa [7] for the synthesis of sandwich complexes with linear/bent palladium arrays and, from a different point of view, by Ren connecting dinuclear complexes to a wide range of conjugated polyenes. [8] From this approach, motifs ranking from RC C-[Ru 2 ] [9] to RC C-[Ru 2 ]-C CR, [10] [Ru 2 ]-(C C) n -[Ru 2 ], [11] and the amazing hexametallic doubly connected [12] with strong intermetallic communication have been prepared ([Ru 2 ] = Ru 2 L 4 , L = binucleating ligand). Linear complexes of higher nuclearity have been less studied in this field, with only few reported examples of trinuclear compounds connected to acetylide units.…”
mentioning
confidence: 99%
“…In parallel with these seminal studies, there have been relevant developments with redoxactive carbon-rich group 8 organometallics. These compounds are ideal candidates for reversible charge storage at the molecular level, [15][16][17][18][19][20] and recently Fehlner, Blum, and Rigaut have independently established that both homo-and heteropolynuclear representatives of this class of molecules can be anchored on conducting silicon [9,10] or gold [21,22] interfaces.The studies of bundles/monolayers on gold have revealed far better conduction through these organometallic substrates than through purely organic analogues of similar length, [21,22] while the studies on silicon surfaces have shown that a given redox state of the immobilized molecules can be generated by application of a suitably chosen electrical potential to this hybrid junction. [9,10] In complementary studies in the field of optics, [23] we have recently demonstrated that electrochemical generation of the various redox congeners of the dinuclear Fe(II)/Ru(II) complex 1 (Scheme 1) [24] provides a means to modulate the linear and nonlinear optical properties of a solution of these compounds.…”
mentioning
confidence: 99%
“…The studies of bundles/monolayers on gold have revealed far better conduction through these organometallic substrates than through purely organic analogues of similar length, [21,22] while the studies on silicon surfaces have shown that a given redox state of the immobilized molecules can be generated by application of a suitably chosen electrical potential to this hybrid junction. [9,10] In complementary studies in the field of optics, [23] we have recently demonstrated that electrochemical generation of the various redox congeners of the dinuclear Fe(II)/Ru(II) complex 1 (Scheme 1) [24] provides a means to modulate the linear and nonlinear optical properties of a solution of these compounds.…”
mentioning
confidence: 99%